Career perceptions among technical and vocational education and training (TVET) students’ towards tourism and hospitality industry - Winne Anak Chengai (2022)
Technical and Vocational Education and Training (TVET) is important to provide skill development in Malaysia based on industry demand. The rationale underlying TVET is to produce graduates with work-ready and develop relevant knowledge and skills. This study aims to investigate the career perception among TVET students towards the tourism and hospitality industry. The design of this study is based on nine dimensions that were used to collect student career perceptions. Data were collected from 117 East Malaysia Polytechnic students between March and May 2020, using purposive sampling techniques. The quantitative method was used, and the data were analysed using the Statistical Package for Social Sciences version 25.0. (SPSS 25.0). Overall, students have a more positive attitude toward tourism and hospitality. However, this study has some negative responses, such as long working hours, a risky working environment, insufficient pay, and managers who do not have tourism or hospitality educational backgrounds. The factor analysis revealed that the five dimensions are retained: industry person congeniality, commitment to work, pay and benefits, co-workers and managers that influence student career perception towards tourism and hospitality industry. Furthermore, there was a strong correlation between pay and benefits and co-worker in this study. This study filled a knowledge gap in the literature, specifically in TVET institutions in Sabah and Sarawak. The findings of this study have contributed to the body of knowledge in terms of the multi-dimensional construct of career perception among TVET students in Malaysia polytechnic towards the tourism and hospitality industry.